Myth, politics and law (Revista Direito em Debate, 2023)
Myth, politics and law will be the subjects discussed in this brief study, so that the purpose here advocated is mainly to discuss the importance of such elements to the world of culture, in general, and to politics and legal science, in a specific way. In short, starting from philosophical presuppositions, going through the essentially analytical method, and trying to arrive at the explanation of political and juridical objectives, the debate will revolve around some subjects that are necessary for a somewhat broader understanding of the correlative phenomenon between political and juridical. Therefore, one will not lose sight of the primary need to establish a firm theoretical correspondence between Philosophy, from the perspective of myth, politics and law, starting from an interdisciplinary approach, establishing dialogue and interlocution between these three strands of the human knowledge.